Activation of innate immunity during development induces unresolved dysbiotic inflammatory gut and shortens lifespan - Kyoko Yamashita; Ayano Oi; Hina Kosakamoto; Toshitaka Yamauchi; Hibiki Kadoguchi; Takayuki Kuraishi; Masayuki Miura; Fumiaki Obata (The Company of Biologists, 2021)
An early-life inflammatory response is associated with risks of age-related pathologies. How transient immune signalling activity during animal development influences life-long fitness is not well understood. Using Drosophila as a model, we find that activation of innate immune pathway Immune deficiency (Imd) signalling in the developing larvae increases adult starvation resistance, decreases food intake and shortens organismal lifespan. Interestingly, lifespan is shortened by Imd activation in the larval gut and fat body, whereas starvation resistance and food intake are altered by that in neurons. The adult flies that developed with Imd activation show sustained Imd activity in the gut, despite complete tissue renewal during metamorphosis. The larval Imd activation increases an immunostimulative bacterial species, Gluconobacter sp., in the gut microbiome, and this dysbiosis is persistent to adulthood. Removal of gut microbiota by antibiotics in the adult fly mitigates intestinal immune activation and rescues the shortened lifespan. This study demonstrates that early-life immune activation triggers long-term physiological changes, highlighted as an irreversible alteration in gut microbiota, prolonged inflammatory intestine and concomitant shortening of the organismal lifespan.